Case Report: A case of tuberculous empyema causing rupture of the diaphragm was misdiagnosed as diaphragmatic hernia - Tao Liu; Ting Yi Zhou; Guang Yu Li; Jing Feng Xu (Frontiers in Medicine)
Tuberculous empyema (TE) is a chronic active infection caused by Mycobacterium tuberculosis that invades the pleural cavity. Initially, fluid accumulates in the pleural space, followed by an influx of neutrophils, which gradually develops into purulent fluid. This process can eventually lead to pleural thickening and calcification, restricting lung expansion and impairing lung function. Additionally, empyema can extend outward through weaknesses in the chest wall, forming abscesses in the soft tissues outside the thoracic cavity. The combination of anti-tuberculosis medications and surgical intervention is a crucial treatment approach for tuberculous empyema. We report a case of tuberculous empyema that invaded the diaphragm, resulting in diaphragmatic rupture and the formation of a subcapsular liver abscess, which was initially misdiagnosed as a diaphragmatic hernia. The patient showed significant improvement and was discharged following surgical treatment.